Jasmonic acid carboxyl methyltransferase regulates development and herbivory‐induced defense response in rice. Issue 6 (17th November 2015) - Qi, Jinfeng; Li, Jiancai; Han, Xiu; Li, Ran; Wu, Jianqiang; Yu, Haixin; Hu, Lingfei; Xiao, Yutao; Lu, Jing; Lou, Yonggen
Abstract: Jasmonic acid (JA) and related metabolites play a key role in plant defense and growth. JA carboxyl methyltransferase (JMT) may be involved in plant defense and development by methylating JA to methyl jasmonate (MeJA) and thus influencing the concentrations of JA and related metabolites. However, no JMT gene has been well characterized in monocotyledon defense and development at the molecular level. After we cloned a rice JMT gene, OsJMT1, whose encoding protein was localized in the cytosol, we found that the recombinant OsJMT1 protein catalyzed JA to MeJA. OsJMT1 is up‐regulated in response to infestation with the brown planthopper (BPH; Nilaparvata lugens ). Plants in which OsJMT1 had been overexpressed (oe‐JMT plants) showed reduced height and yield. These oe‐JMT plants also exhibited increased MeJA levels but reduced levels of herbivore‐induced JA and jasmonoyl‐isoleucine (JA‐Ile). The oe‐JMT plants were more attractive to BPH female adults but showed increased resistance to BPH nymphs, probably owing to the different responses of BPH female adults and nymphs to the changes in levels of H2 O2 and MeJA in oe‐JMT plants. These results indicate that OsJMT1, by altering levels of JA and related metabolites, plays a role in regulating plant development and herbivore‐induced defense responses in rice. Abstract : Jasmonic acid (JA) and related metabolites play key roles in plant defense and growth. Our study shows that a JA carboxyl methyltransferase, by methylating JA to methyl jasmonate, alters levels of JA and related metabolites and thereby regulates plant development as well as herbivore‐induced defense responses in rice.